2019
DOI: 10.1177/2158244019834453
|View full text |Cite
|
Sign up to set email alerts
|

Caring for One’s Wife With Dementia—at Home: Older Husbands’ Experiences With Managing Challenges of Everyday Life

Abstract: More than 80,000 Norwegians live with dementia. Most caregivers for people with dementia are spouses, and women outnumber men. Due to an aging population, and women's higher risk of dementia as well as men's increased life expectancy, the number of male caregivers will rise. There are some differences in the caregiving roles of men and women. Research suggest that males report lower burden and depression than female caregivers, but some men struggle to adjust to the caregiver role, and men are less likely to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
8
0
1
Order By: Relevance
“…One of the most sought-after relationships to address loneliness amongst older people are those based on closeness and intimacy (Cohen-Mansfield and Eisner, 2020), therefore it could be argued that the perceived loss of the close spousal relationship experienced by older spousal male care-givers in the current study exacerbated their loneliness. Rykkje and Tranvåg (2019) explored older husband's experiences of caring for their wives in Norway (N = 5), and revealed that a decline in mutual interests led to a sense of loneliness for study participants, often underpinning their choice of actions. For example, some husbands chose to stop pursuing mutual interests (such as going to the theatre) after their wife's interest faded.…”
Section: Discussionmentioning
confidence: 99%
“…One of the most sought-after relationships to address loneliness amongst older people are those based on closeness and intimacy (Cohen-Mansfield and Eisner, 2020), therefore it could be argued that the perceived loss of the close spousal relationship experienced by older spousal male care-givers in the current study exacerbated their loneliness. Rykkje and Tranvåg (2019) explored older husband's experiences of caring for their wives in Norway (N = 5), and revealed that a decline in mutual interests led to a sense of loneliness for study participants, often underpinning their choice of actions. For example, some husbands chose to stop pursuing mutual interests (such as going to the theatre) after their wife's interest faded.…”
Section: Discussionmentioning
confidence: 99%
“…Aviopuolisot voivat tuntea myös surua, turhautumista, epävarmuutta ja syylli syyttä muistellessaan yhteistä elämäänsä sekä heitä yhdistäviä asioita ja kiinnostuksen koh teita, jotka he olivat aiemmin jakaneet aviopa rina (Boylstein & Hayes 2012;Hernandez ym. 2019;Rykkje & Tranvåg 2019).…”
Section: Muistisairaus Ja Käytösoireet Parisuhteessaunclassified
“…Moreover, one of the essential elements of the couplehood, namely emotional and intellectual reciprocity, may disappear as the condition progresses [ 2 , 3 , 13 , 14 ]. These changes may evoke sadness, frustration, resentment, and guilt as they recall the life and interests previously shared in the couplehood [ 8 , 12 , 15 ].…”
Section: Introductionmentioning
confidence: 99%